Abandoned Children: The Legacy Of Poverty That Never Ends Its Handling - Tiar Handayani; Wulani Wulani; Mukarto Siswoyo; Siti Khumayah (International Journal Labs, 2024)
Abandoned children have many experiences that come from harsh environments and not all of them are accepted by society. Therefore, special approaches and treatments are needed to help them develop their thinking processes, teach them how to build relationships between the past, present and future, and direct them towards patterns of behavior that are acceptable to society. This study uses qualitative research methods. This study uses qualitative data where this data is obtained from selected informants who are relevant and have the competence to provide the research data selected by the researcher. Data collection techniques were collected through documentation studies, interviews and observations. The results of this study show that the number of abandoned children in Cirebon City is around 70 people. The Cirebon city social service has a program to foster abandoned children, namely GSM, social guidance, family, understanding parenting and teaching and learning activities. This study uses the implementation theory of Van Meter and Van Horn The implementation stage can be seen from 6 important variables when achieving an implementation, namely: objectives and policy size, attitudes (disposition) of implementers, infrastructure and human resources, characteristics of implementing agents, communication activities and implementers between organizations, as well as the political, social and economic environment. The results of this study show that the policy of the Abandoned Children Development program at the Cirebon City Social Service is not optimal because of low budget sources, so the implementation of the policy has not fully met the standards. Social protection is aimed at helping the poor and vulnerable population, especially those who experience other welfare problems.